Effect of β-alanine on the athletic performance and blood amino acid metabolism of speed-racing Yili horses - Li, Xiaobin; Ma, Jun; Li, Haiying; Li, Hai; Ma, Yuhui; Deng, Haifeng; Yang, Kailun (Frontiers in Veterinary Science, 2024)
The objective of this study was to examine the effects of supplemental β-alanine feeding on the athletic performance of Yili horses involved in speed racing, focusing on alterations in plasma free amino acid patterns pre and post exercise. Additionally, the research aimed to evaluate the effects of carnosine on the plasma acid-base buffering capacity and antioxidant levels in these horses. Twelve Yili horse stallions, averaging 3 years in age and 346.50±21.39 kg in weight, were chosen and randomly divided into two groups: a control group and a test group, each comprising six horses. The control group received a supplementation of 300 mg/kg BW/day of α-alanine, while the test group received 300 superoxide dismutase, glutathione peroxidase, and total antioxidant capacity significantly increased both before and after the race, while the content of malondialdehyde, an oxidation product, exhibited an extremely significant decrease immediately after the race. These outcomes suggest that the addition of β-alanine significantly augmented antioxidant levels during high-intensity exercise in Yili horses.Consequently,it reduced post-exercise injuries and accelerated the recovery process after exercise.